Water permeability and carbonation on foamed concrete - Sulaiman, Suhaizad (2011)
Foamed concrete is a controlled density low strength material with density ranging from 300 kg/m3 to 1800 kg/m3 suitable for construction of walls. The acceptance of foamed concrete blocks and panels by the Construction Industry Development Board of Malaysia as components of industrialized building system has promoted its commercial applications. It is made of cement, fine sand, water and preformed foam. Its self-compacting properties have enhanced productivity for mass production. Previous studies revealed findings on the use of large volume partial cement replacement materials without adverse effect on its physical and mechanical properties. This study focused mainly on the effect of the density of foamed concrete on carbonation and water permeability. The ability to vary the density of foamed concrete is considered a unique characteristic compared with normal concrete. Carbonation is usually considered as a negative impact on reinforced concrete. It is the process of pH reduction of concrete from 12.6 to 9.0 in the presence of carbon dioxide and moisture. The reduction of alkalinity means the loss of protection against corrosion to steel bars embedded within concrete. However, for nonstructural applications of foamed concrete in wall construction without steel bars or with the use of corrosion inhibitor, carbonation is turned into an advantage for sustainable construction. The ability of foamed concrete to speed up the absorption of carbon dioxide is an important aspect to be explored for its potential use in reducing carbon footprint from the construction industry. The objective of this study is to explore a relationship between carbonation depth, water permeability and the density of foamed concrete. The laboratory tests were conducted on concrete cubes and prisms for up to one and a half years. The water permeability method was developed based on ISO/DIS 7031. The test results indicate that increasing density of foamed concrete tends to reduce its water permeability and carbonation depth. The plot of carbonation depth against permeability coefficient produces a linear relationship. The rate of carbonation was found to be inversely proportional to the square root of density. An empirical formula incorporating density as a variable based Currie’s formula is produced. This finding is expected to excite researchers who are concerned with the use of concrete for sustainable construction. Its tendency to absorb carbon dioxide faster than normal concrete from the atmosphere in the carbonation process is expected to lead to widespread use of foamed concrete for environmental and economical advantages.